ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI ALOKASI BELANJA MODAL (Studi pada Pemerintah Kabupaten/Kota di Jawa Tengah Tahun 2015-2017) - Mega Ajeng Kartikasari; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
This research is aimed to empirically examine the relation between regional income per capita, gross domestic product of region, general allocation fund, local revenue, financial independence ratio, and allocation of capital expenditure. The dependent variable in this research is allocation of capital expenditure. The independent variables in this research are regional income per capita, gross domestic product of region, general allocation fund, local revenue and financial independence ratio.The sample of this research consist of 35 Regency/Municipality in the Province of Central Java in the period 2015-2017. This research use quantitative method by using report data realization of local budget revenues and expenditures (APBD) and also the tables of gross domestic product of region (PDRB) Regency/Municipality in the Province of Central Java. The analytical method that was used is multiple linear regression analysis. The results of this research shows that the variables of regional income per capita, general allocation fund, and local revenue have significant effect on the allocation of capital expenditure. It means that, in determining the amount of income allocated for capital expenditure, local governments should consider regional income per capita, general allocation fund, and local revenue. While the variables of gross domestic product of region and financial independence ratio do not have significant effect on the allocation of capital expenditure.